Legal nature of intensifiers in some commercial contracts - Janković, Svetislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
In the article, author considers the legal nature of intensifiers in commercial contracts. The intensifier is the term created and tailored by the author with an intention to synthesize the clauses in contracts aimed to increase and intensify the primary contract obligation. The first step in research has been taken from the dichotomy of the surety and insurance as a potential explanation of intensifiers. But, unsatisfied with them, the author goes deeply further explaining the nature of intensifiers with the feature of aleatory, to finally conclude that mentioned intensifiers are, in fact, causal condition. This conclusion is derived from the fact that activation of the intensifier is descended from the realization of future uncertain circumstances which are also independent from the contractors.